The Impact of Covid-19 on the Global Economy and Migration - Adli, Maryam; Saleem, Amama; Saleem, Tamima; Adli, Hawa; Adli, Maria (Advances in Social Sciences Research Journal, 2021)
The World Health Organization stated COVID-19 a global pandemic, it has quickly spread all over the world, posing immense health, environmental and social challenges to the global population. The coronavirus outbreak is critically interrupting the global trade and has shattered the core sustaining pillars of the modern world economies. Concerns have been raised about policy changes, enforcement actions, immigrant detention, and deportation practices during the outbreak. The impact of COVID-19 on these trends implies new dimensions for global governance and organizations. This article seeks to highlight Azerbaijan's problems in the context of the battle against a pandemic. Because a country's economy has been impacted, a comprehensive study may give a better understanding of the results, illuminating the areas that require more assistance and growth.